A gamified peer assessment model for on-line learning environments: An experiment with MeuTutor - Tenório, Thyago; Bittencourt, Ig Ibert (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2016: Anais do XXIX Concurso de Teses e Dissertações, 2016)
Though the on-line learning environments provide scalable and automatic ways to present a content, forums and evaluate the progress of the students, they are still limited in their ability to evaluate complex activities such as correction of essays. Facing this issue, Peer Assessment (PA) offers a powerful solution. However, a major problem found when using PA is the presence of inadequate behaviours from students, which affect the learning and evaluation system. In this sense, this paper proposes a gamified peer assessment model, where the gamification elements improvement the motivational aspect of the students. In the experiments conducted, it was concluded that there were no statistical variations between the grades obtained compared to the experts, the correction time was reduced and the cost involved decreased 72.4%. The gamification encouraged students to use the platform: increased access (+64.28%), essays performed (+10.53%) and essays corrected (+20%).